Jimpa [videorecording (DVD)] - Hyde, Sophie; Cormack, Matthew; Colman, Olivia; Mason-Hyde, Aud; Lithgow, John, 1945-; Henshall, Daniel, 1983-; Box, Kate; Farren, Eamon; Smith, Zoë Love (Kino Lorber, 2026)
Filmmaker Hannah takes her trans nonbinary teenager Frances to Amsterdam, to visit their gay grandfather lovingly known as Jimpa. But Frances' desire to stay with Jimpa for a year abroad means Hannah is forced to reconsider her beliefs about parenting, and the stories she has long told about her family. Funny, accessible, full of sadness and joy, and with a wonderful multi-generational cast, Jimpa celebrates LGBTQ+ culture across three generations.